Identificación de individuos de jaguares (Panthera onca) y pumas (Puma concolor) a partir de morfometría de sus huellas (Carnivora: Felidae) - Isasi Catalá, Emiliana; R. Barreto, Guillermo (Revista de Biología Tropical, 2008)
Estimating feline abundance becomes particularly difficult, sometimes impossible, due to their elusive behavior and extensive space requirements. Available techniques are expensive and/or poorly efficient, therefore alternative methods are needed. The objective of this study was to assess the possibility of identifying individual jaguars and pumas based on morphometric analyses of their tracks. The footprints of five jaguars and four pumas were drawn and the foot (hind or fore foot, left or right foot) and the substrate were recorded. We took 16 measures from each footprint including lengths, widths, areas and angles. Variables were analyzed by using Principal Component Analysis (PCA) and substituted by the first Principal Component (PC) (> 70 % variance). We assessed the effect of the substrate and type of foot by means of paired t-student tests, and found differences between fore and hind feet and footprints from the same indi-vidual when made on soil or sand. No differences were found between right or left feet. The footprints changed over time as revealed by Multiple ANOVA. Different individuals could be identifyied based on discriminant analyses with more than 70 % confidence. We conclude that this method is feasible and can be useful when studying endangered felines.